Prevalence and Clinical Characteristics of Wheezing in Children in the First Year of Life, Living in Cuiabá, Mato Grosso, Brazil [Prevalência E Características Clínicas Da Sibilância Em Crianças No Primeiro Ano de Vida, Residentes Na Cidade de Cuiabá, Mato Grosso, Brasil] - Mallol-Villablanca, E (Sao Paulo Pediatric Society, 2014)
Objective: To evaluate the prevalence and the clinical characteristics of wheezing in infants aged 12 to 15 months in the city of Cuiabá, Mato Grosso State, Midwest Brazil.Methods: Parents and/or guardians of infants were interviewed and completed a written standardized questionnaire of the Estudio Internacional de Sibilancia en Lactantes (EISL) – phase 3 at primary healthcare clinics at the same day of children vaccination or at home, from August of 2009 to November of 2010.Results: 1,060 parents and/or guardians completed the questionnaire, and 514 (48.5%) infants were male. Among the studied infants, 294 (27.7%) had at least one episode of wheezing during the first year of life, beggining at 5.8±3.0 months of age, with a predominance of male patients. The prevalence of occasional wheezing (<3 episodes of wheezing) was 15.0% and recurrent wheezing (?3 episodes) was 12.7%. Among the infants with recurrent wheezing, the use of inhaled ?2-agonist, oral corticosteroid, leukotriene receptor antagonist, as well as night symptoms, respiratory distress, and hospitalization due to severe episodes were significantly more frequent. Physician-diagnosed asthma was observed in 28 (9.5%) of the wheezing infants. Among the wheezing infants, 80 (27.7%) were diagnosed with pneumonia, of whom 33 (11.2%) required hospitalization; neverthless, no differences between occasional and recurrent wheezing infants were found.Conclusions: The prevalence of recurrent wheezing and physician-diagnosed asthma in infants were lower compared with those observed in other Brazilian studies. Recurrent wheezing had early onset and high morbity. © 2014 Sociedade de Pediatria de São Paulo. Published by Elsevier Editora Ltda. All rights reserved.